Predictors of recurrent/residual disease after loop electrosurgical excisional procedure. Issue 4 (19th January 2016) - Chikazawa, Kenro; Netsu, Sachiho; Motomatsu, Shigeru; Konno, Ryo
Abstract: Aim: The aim of this study was to identify predictors of recurrent/residual disease for management after loop electrosurgical excisional procedure. Methods: We retrospectively reviewed 178 patients with cervical intraepithelial neoplasia grade 3 and microinvasive squamous cell carcinoma who underwent the loop electrosurgical excisional procedure between April 2011 and March 2014. Endocervical/ectocervical margin status, endocervical curettage (ECC) status, and maximum width of cervical intraepithelial neoplasia were assessed. Patients were followed up for 6–12 months. Results: Patients with endocervical margin involvement were significantly older and those with ectocervical margin involvement were significantly younger than patients with no margin involvement ( P = 0.02 for both comparisons). ECC‐positive patients were significantly older than ECC‐negative patients ( P = 0.049). There was a significant difference in the mean width of the cervical intraepithelial neoplasia between women with ectocervical involvement and those without ecto‐ or endocervical involvement (10.2 ± 3.1 mm vs 7.3 ± 3.5 mm, P = 0.0002). The odds ratios for possible recurrent/residual disease for endocervical involvement, ectocervical involvement, and ECC‐positivity were 2.1 (0.5–8.4), 3.2 (1.3–7.9), and 6.8 (1.4–32.1), respectively. However, while most ECC‐positive patients underwent a second surgery, most patients with ectocervical involvement did not need further treatment. Conclusion: Older age and ECC were significantly associated with endocervical margin involvement; younger age and width of cervical intraepithelial neoplasia were associated with ectocervical margin involvement. Ectocervical margin involvement significantly increased the risk of possible recurrent/residual disease; however, these patients might recover naturally. ECC‐positivity significantly increased the risk of recurrent/residual disease.